2006
DOI: 10.1007/s10886-006-9183-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sunflower (Helianthus annuus L.) Extracts Upon Reserve Mobilization and Energy Metabolism in Germinating Mustard (Sinapis alba L.) Seeds

Abstract: One commonly observed effect of phytotoxic compounds is the inhibition or delay of germination of sensitive seeds. Mustard (Sinapis alba L.) seeds were incubated with aqueous extracts of sunflower (Helianthus annuus L.) leaves. Although sunflower phytotoxins did not influence seed viability, extracts completely inhibited seed germination. Inhibition of germination was associated with alterations in reserve mobilization and generation of energy in the catabolic phase of germination. Degradation of lipids was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
2
26
0
5
Order By: Relevance
“…Assim como os resultados da cultivar CD232, sementes de mostarda (Sinapis alba L.) também sofreram inibição na porcentagem de germinação quando submetidas ao extrato aquoso da parte aérea do girassol (KUPIDLOWSKA et al, 2006). Para a cultivar CD213RR (soja transgênica) foi observada diferença significativa na variável porcentagem de germinação entre as sementes da testemunha e as submetidas à maior concentração do extrato aquoso de girassol (100%), coincidindo com o maior tempo médio de germinação.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Assim como os resultados da cultivar CD232, sementes de mostarda (Sinapis alba L.) também sofreram inibição na porcentagem de germinação quando submetidas ao extrato aquoso da parte aérea do girassol (KUPIDLOWSKA et al, 2006). Para a cultivar CD213RR (soja transgênica) foi observada diferença significativa na variável porcentagem de germinação entre as sementes da testemunha e as submetidas à maior concentração do extrato aquoso de girassol (100%), coincidindo com o maior tempo médio de germinação.…”
Section: Resultsunclassified
“…Entretanto, alguns estudos demonstram esta mesma atividade alelopática inibitória do girassol sobre espécies vegetais cultivadas como a mostarda (Sinapis alba L.), trigo (Triticum spp. ), sorgo (Sorghum bicolor L. Moench), ressaltando a importância de mais estudos quanto à fitotoxidade do girassol para sua indicação em sistemas de rotação e sucessão de culturas (KUPIDLOWSKA et al, 2006;BERNAT et al, 2004).…”
Section: Introductionunclassified
“…Leaf powder (10 g dry weight [DW]) was extracted for 24 hr in 100 ml of distilled water at 20°C. The obtained 10% (w/v) extract was filtered through filter paper and used as a source of phytotoxins Kupidłowska et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Undisturbed reserve mobilization is an important requirement for germination during the catabolic process just after liquid imbibition (Kupidłowska et al 2006). Rudrappa et al (2007) found that the root-secreted allelochemicals from P. australis deployed a reactive oxygen species (ROS) that is responsible for stress conditions on the affected plant.…”
Section: Introductionmentioning
confidence: 99%